2022
DOI: 10.1039/d2ra04391b
|View full text |Cite
|
Sign up to set email alerts
|

A green process for recycling and synthesis of cathode materials LiMn2O4from spent lithium-ion batteries using citric acid

Abstract: In the process of recycling spent lithium-ion batteries, citric acid is only used as a chelating agent to resynthesize new cathode materials by a sol-gel process or as a precipitant to separate Mn ions and Li ions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…The electrochemical performance test showed that the regenerated cathode material had an excellent electrochemical performance, and the discharge curves of LiMn 2 O 4 have been shown in Figure 7B. Similarly, Wang J. et al (2022) used citric acid and sol-gel method to regenerate LMO batteries but did not use glucose as a reducing agent. It explored the influence of citric acid concentration, leaching time, and solid-liquid ratio on the leaching process.…”
Section: Single-type Regeneration Of Spent Libsmentioning
confidence: 99%
“…The electrochemical performance test showed that the regenerated cathode material had an excellent electrochemical performance, and the discharge curves of LiMn 2 O 4 have been shown in Figure 7B. Similarly, Wang J. et al (2022) used citric acid and sol-gel method to regenerate LMO batteries but did not use glucose as a reducing agent. It explored the influence of citric acid concentration, leaching time, and solid-liquid ratio on the leaching process.…”
Section: Single-type Regeneration Of Spent Libsmentioning
confidence: 99%
“…Various techniques have been utilized to develop LIB recycling, however, hydrometallurgy is frequently employed in industrial sectors as a cost-effective and environmentally sustainable method to extract valuable metals from spent LIBs due to its higher efficiency and lower harmful gas emissions. 20–22 Several investigations have been conducted on the leaching of critical metals using both inorganic acids (such as HCl, 23 HNO 3 , 24 H 2 SO 4 , 25,26 and H 3 PO 4 27 ) and organic acids (such as citric acid, 28,29 malic acid, 30,31 lactic acid, 32 ascorbic acid, 33 oxalic acid, 34 and succinic acid 35 ). Compared to inorganic acids, organic acids are almost natural and sustainable.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrometallurgical methods have been employed by Wang et al to recycle spent batteries, where the Al foil was separated at 550 °C and then leached with 1.0 M citric acid to regenerate the LMO. [19] Therefore, recycling spent LMO batteries at a low cost and high efficiency holds tremendous importance. DOI: 10.1002/ente.202300617 Herein, a facile method with high efficiency is proposed for the separation and regeneration of LiMn 2 O 4 (LMO) cathode material for spent lithium-ion batteries through a simple heat treatment method.…”
Section: Introductionmentioning
confidence: 99%